Educational Function as a Factor in Creating the Gravity Area of the city of Tuzla - Bećirović, Almira; Kudumovic Dostovic , Fadila (Journal for Geography, 2022)
The strong industrial development and urbanization of Tuzla since the second half of the 20th century influenced, among other things, the development of the educational function and the opening of schools of various educational levels and professions. Also, the educational function has influenced significant changes in the educational structure of the population, as well as the initiation of pupils and students from settlements whose place of residence is closer or further from the educational center. This led to a »migration wave« of pupils and students towards Tuzla as the educational center of Northeastern Bosnia. The paper presents an analysis of the contemporary educational function of the city of Tuzla and its changes from the mid-fifties of the last century to today, as well as changes in the educational structure of the population as one of the important indicators of the educational function. When analyzing the gravity area of the educational function of the city, the paper uses data on the territorial range of daily migrations of pupils and students towards the center of education, obtained through field research.
Keywords: City of Tuzla; daily migration; educational function; gravity area